PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI DISTRIK TINNGINAMBUT KABUPATEN PUNCAK JAYA - tabuni, yoten; suroso, adi; rusno (Jurnal Riset Mahasiswa Manajemen, 2025)
This research aims to determine how much influence service quality has on the level of community satisfaction in Tinnginabut District, Puncak Jaya Regency. This study uses a quantitative approach. The subjects of this research were people who had interests in the Tinnginabut District, Puncak Jaya Regency and a sample of 96 people was taken. The data collection method uses a questionnaire. The analysis technique used is Simple Regression Analysis. Based on simple linear regression analysis, the regression equation Y= 18.347 + 0.448 is obtained. The regression coefficient value of 0.448 states that if the service quality is at the 1 unit level, then the job satisfaction value is 0.448. Based on hypothesis testing with the t test, the t-count value was 7.010 > t-table 1.986, so H0 was rejected and Ha was accepted, which means that partially there is a positive influence of service quality on community satisfaction at the Tinginnambut District office, Puncak Jaya Regency. Based on the results of the coefficient of determination test, the R value = 0.586 and the R square (R2) value is 0.343. This shows that the influence of service quality is 34.3% while the remaining 65.7% is influenced by other factors not examined in this research.